Patient safety and staffing in emergency departments - Ecklor, Nekole (My University, 2009)
The purpose of this study was to investigate and describe nurse staffing methods, nurse skill mix, and patient safety in emergency departments (EDs) in order to address the question: How does nurse staffing impact patient safety in EDs? Although studies have revealed an association between nurse staffing and patient safety for inpatient populations, there is limited research on the relationship between nurse staffing methods, nurse skill mix, and patient safety in EDs. The question was evaluated by examining the ED as a system using Katz and Kahn's Open Systems Theory. In this framework, patients enter the ED department (system) and their outcome (patient safety) is influenced by nurse staffing (throughput). A descriptive cross-sectional design was used to investigate nurse staffing methods, nurse skill mix, and the impact on patient safety. The setting was EDs in the state of Wisconsin that were listed with the American Hospital Association (AHA). All ED managers on the AHA's list received the Emergency Department Survey (EDS). The EDS is a 12-item survey that investigated the nurse staffing method, nurse skill mix, and measured patient safety by examining the frequency of patient safety incidents in EDs. Fifty-seven usable surveys were returned out of the 115 distributed. With a research standard of 95% confidence level, 89 surveys were needed to produce meaningful findings. The statistical analyses used to analyze the collected data and answer the research question were descriptive, analysis of covariance (ANCOVA), qualitative analysis, and multiple regressions. Findings from the statistical analysis are: (a) Industrial engineering method of nurse staffing had a higher level of errors than other methods; (b) Emergency medical technician-paramedics (EMT-P) were four times more likely to have a correlation of medication errors and sentinel events combined; (c) Registered nurses (RNs) have an inverse association with a positive impact on patient safety; (d) Incorrectlabeling comprised 13.5% of total errors; (e) The largest category in the variable of patient safety was elopement, with 40% of reported errors; (f) Patient falls had an inverse correlation. with licensed practical nurses (LPNs) and EMT-Ps; (g) Elopement had a positive correlation with RNs and EMT-Ps and an inverse correlation with LPNs; (h) Incorrect identification was inversely correlated with LPNs and unlicensed assistive personnel (UAPs) and positively correlated with EMT-Ps; (i) Incorrect specimen labeling was inversely correlated with LPNs and EMT-Ps.
A Thesis Submitted in Partial Fulfillment of the Requirements for the Degree of Master of Science - Nursing - Family Nurse Practitioner --University of Wisconsin-Oshkosh, 2008
Keywords: Nurse and patient; Emergency Nursing -- organization & administration; Nursing, Safety measures; Nursing Staff, Hospital